Extremely preterm infants born outside a provincial tertiary perinatal center and transferred postnatally associated with poor outcomes: a real-world observational study - Peng, Sicong; He, Xianjing; Xia, Shiwen (Frontiers in Pediatrics, 2024)
Introduction: Extremely preterm infants (EPIs) have high morbidity and mortality, and are recommended to delivery in a tertiary perinatal center (inborn). However, many EPIs in central China are still born in the lower-level hospitals and transferred postnatally whose outcomes remain to be investigated.EPIs admitted to the Department of Neonatology of Maternal and Child Health Hospital of Hubei Province from January 2013 to December 2022 were recruited retrospectively, and divided to the control (inborn) and transferred group (born in the other hospitals). The neonatal and maternal characteristics, neonatal outcomes and the treatment of survival EPIs were analyzed.Results: A total of 174 and 109 EPIs were recruited in the control and transferred group, respectively. EPIs in the transferred group have heavier birth weight and lower proportion of multiple pregnancy than the control group (all P < 0.05). The proportions of antenatal steroids, magnesium sulfate, cesarean delivery, premature rupture of membrane ≥ 18 hours, gestational diabetes, and amniotic fluid abnormalities were lower in the transferred group (all P < 0.05). The survival rates (64.22% vs 56.32%), proportions of severe periventricular-intraventricular hemorrhage (PIVH) (11.93% vs 11.49%), severe bronchopulmonary dysplasia (sBPD) (21.05% vs 20%), and severe retinopathy of prematurity (ROP) (24.77% vs 20.11%) were similar in the transferred and control groups (all P > 0.05). However, transferred group had higher proportions of severe birth asphyxia (34.86% vs 13.22%, P < 0.001), PIVH (42.20% vs 29.89%, P = 0.034) and extrauterine growth retardation (EUGR) (17.43% vs 6.32%, P = 0.003). Less utilization of surfactant was found in the transferred group among survival EPIs (70.00% vs 93.88%, P < 0.001). Conclusion: EPIs born outside a tertiary perinatal center and transferred postnatally did not have significantly higher mortality and rates of severe complications (severe PIVH, severe ROP, and sBPD), but there may be an increased risk of severe asphyxia, PIVH and EUGR. It may be caused by the differences in maternal and neonatal characteristics as well as management. Further follow-up is needed to compare neurodevelopmental outcomes, and it is recommended to transfer the EPIs in utero to reduce the risks of poor physical and neurological development.